rancang bangun aplikasi sempoa berbasis android - ashari setiawan; jusak jusak; teguh sutanto (Jurnal Sistem Informasi Universitas Dinamika, 2015)
To be able master the abacus, it requires plenty of time and intensive training to master the operational of the abacus. Although in several schools and in institutions abacus course has been taught, but it does guarantee to be able to master the abacus. Especially for someone who have not been taught the abacus in school and have not completed a course the abacus would have trouble even those who are not familiar with the abacus. To be master the abacus we must have books about how to learn the abacus and we must have a real abacus tool for exercise the abacus.One of solution is to be able master the abacus with developed application using smartphone technology based on android operating system can be used as a tool for daily exercise in order to familiarize with the abacus.in a series of trials that have been done, the abacus application can be running on some version of the android operating system such as Gingerbread, HoneyComb, Ice cream sandwich, Jelly bean and Kitkat. On this application there are two learning modules consisting of learning abacus and learning arithmetic using abacus. In addition to the learning modules, the application also features learning abacus and learn arithmetic operations.This application also provides exercises, on the features of this exercise consists of the exercises of arithmetic and a matter of exercise where users can perform exercises to hone his ability to learn the abacus.